Complementary Therapies and Medicines and Reproductive Medicine - Smith, Caroline A.; Armour, Mike; Ee, Carolyn (Seminars in Reproductive Medicine, 2016)
Complementary therapies and medicines are a broad and diverse range of treatments, and are frequently used by women and their partners during the preconception period to assist with infertility, and to address pregnancy-related conditions. Despite frequent use, the evidence examining the efficacy, effectiveness, and safety for many modalities is lacking, with variable study quality. In this article, we provide an overview of research evidence with the aim of examining the evidence to inform clinical practice. During the preconception period, there is mixed evidence for acupuncture to improve ovulation, or increase pregnancy rates. Acupuncture may improve sperm quality, but there is insufficient evidence to determine whether this results in improved pregnancy and live birth rates. Acupuncture can be described as a low-risk intervention. Chinese and Western herbal medicines may increase pregnancy rates; however, study quality is low. The evaluation of efficacy, effectiveness, and safety during the first trimester of pregnancy has most commonly reported on herbs, supplements, and practices such as acupuncture. There is high-quality evidence reporting the benefits of herbal medicines and acupuncture to treat nausea in pregnancy. The benefit from ginger to manage symptoms of nausea in early pregnancy is incorporated in national clinical guidelines, and vitamin B6 is recommended as a first-line treatment for nausea and vomiting in pregnancy. The safety of ginger and vitamin B6 is considered to be well established, and is based on epidemiological studies. Acupuncture has been shown to reduce back pain and improve function for women in early pregnancy. There is little evidence to support the use of cranberries in pregnancy for prevention of urinary tract infections, and chiropractic treatment for back pain. Overall the numbers of studies are small and of low quality, although the modalities appear to be low risk of harm.
Keywords: complementary therapies and medicines; pregnancy; preconception; health